2011
DOI: 10.3109/1354750x.2011.628048
|View full text |Cite
|
Sign up to set email alerts
|

Host biomarkers of clinical relevance in tuberculosis: review of gene and protein expression studies

Abstract: With this review we hope to provide a reliable guideline for biomarker studies in tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…44 In a recent review, John et al suggested that lower IL-12 and higher IL-4 and IL-10 expression in both unstimulated and antigen-stimulated cultures should be promising to discriminate TB disease from LTBI. 12 As other studies, we did not replicate these observations. 45e48 Several factors may explain discrepancies between studies.…”
Section: Discussionsupporting
confidence: 37%
See 1 more Smart Citation
“…44 In a recent review, John et al suggested that lower IL-12 and higher IL-4 and IL-10 expression in both unstimulated and antigen-stimulated cultures should be promising to discriminate TB disease from LTBI. 12 As other studies, we did not replicate these observations. 45e48 Several factors may explain discrepancies between studies.…”
Section: Discussionsupporting
confidence: 37%
“…11 Multicytokine responses, more representative of the immune status of the host, might also identify cytokine profiles associated with latency, progression or dissemination. 12 Despite the critical need for improved diagnosis of TB in children and the poor knowledge of the mechanisms responsible for the greatest severity of TB infection during childhood, studies that simultaneously measured multiple chemokines and/or cytokines in pediatric infection are anecdotical. 13e15 The primary aim of this study was to explore cytokine/ chemokine responses to QFTB peptides in order to improve diagnosis and staging of M.tb infection.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of several cytokines, including interleukin-6 (IL-6), IL-10, IL-15, chemokine (C-X-C) motif ligand (CXCL)/interferon gamma-inducible protein 10 (IP-10), and monocyte chemoattractant protein 2 (MCP-2), were significantly higher in TB patients than in healthy controls (7,11,(18)(19)(20)(21); although these finding suggest important roles for these factors in disease pathogenesis, they are not sufficient for diagnosing Citation Jeong YH, Hur Y-G, Lee H, Kim S, Cho J-E, Chang J, Shin SJ, Lee H, Kang YA, Cho S-N, Ha S-J. 2015.…”
mentioning
confidence: 99%
“…The levels of several cytokines, including interleukin-6 (IL-6), IL-10, IL-15, chemokine (C-X-C) motif ligand (CXCL)/interferon gamma-inducible protein 10 (IP-10), and monocyte chemoattractant protein 2 (MCP-2), were significantly higher in TB patients than in healthy controls (7,11,(18)(19)(20)(21); although these finding suggest important roles for these factors in disease pathogenesis, they are not sufficient for diagnosing active as opposed to latent infections. Several studies have also suggested that biomarker combinations such as IFN-␥Ϫtumor necrosis factor alpha (TNF-␣), IFN-␥ϪIL-2, IFN-␥ϪIL-4, and IL-15ϪMCP-1 might be more sensitive than single markers (18,(22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation